2021
DOI: 10.1371/journal.pone.0249165
|View full text |Cite
|
Sign up to set email alerts
|

TBDBT: A TB DataBase Template for collection of harmonized TB clinical research data in REDCap, facilitating data standardisation for inter-study comparison and meta-analyses

Abstract: Clinical tuberculosis research, both within research groups and across research ecosystems, is often undertaken in isolation using bespoke data collection platforms and applying differing data conventions. This failure to harmonise clinical phenotype data or apply standardised data collection and storage standards in turn limits the opportunity to undertake meta-analyses using data generated across multiple research projects for the same research domain. We have developed the Tuberculosis DataBase Template (TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…The REDCap consortium currently comprises of more than 4000 institutions in 137 countries and membership has the added advantage of free access to technical support and improvements to the platform [14,18]. In addition, using REDCap as the hosting platform, has the added advantage of having a single database for capturing and storing all research related data and this functionality was demonstrated for a Tuberculosis database (TBDBT) by Allie et al [19].…”
Section: E-consent Platformmentioning
confidence: 99%
“…The REDCap consortium currently comprises of more than 4000 institutions in 137 countries and membership has the added advantage of free access to technical support and improvements to the platform [14,18]. In addition, using REDCap as the hosting platform, has the added advantage of having a single database for capturing and storing all research related data and this functionality was demonstrated for a Tuberculosis database (TBDBT) by Allie et al [19].…”
Section: E-consent Platformmentioning
confidence: 99%